Legal providing of aerospace industry activity of Ukraine: the state and perspectives of perfections - Бєглий, О. В.; Боярська, З. І.; Єряшов, Є. К. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
The article analyzes history of becoming of national space legislation and new aspects of legal regulationof national space activity by the space law mechanisms of Ukraine.